A Model of Deformation Geometry in Pipe Bending Processes - Śloderbach, Z. (Engineering Transactions, 1999)
The paper presents a complete set of geometric relationships for logarithmic measures of longitudinal, circumferential and radial strains arising in bending of thin- and thick-walled pipes. The strain can be determined at each plane parallel to the principal plane of bending and at each plane perpendicular to them, so that each point of the bending zone is accounted for. The relationships have a direct reference to engineering practice since they express strains as functions of pipe geometry and bending process variables. The calculation results were compared with experimental data for the bend angle equal to 180° and the bending zone range index equal to 1 and 3. Suitable plots are incorporated.